Kearifan Lokal Masyarakat Dalam Membangun Kerukunan Umat Beragamadi Kota Kupang Nusa Tenggara Timur (NTT) - Moh. Mul Akbar Eta Parera; Marzuki Marzuki (Universitas Andalas, 2020)
Indonesia is a multicultural and diverse nation. one form of diversity in Indonesia is the issue of religion. Diversity in terms of religion can trigger conflict, which can damage Indonesia's culture which is so tolerant among fellow religious communities. Indonesia has the values of local wisdom that form the basis for the creation of religious harmony must be maintained and preserved. This study used a qualitative approach to the type of case study research. This research aims to determine the harmony of religious community trough local wisdom. The results showed that religious harmony in the perspective of local wisdom in the city of Kupang through: Nusi (cooperation). Butukila (bond and hold a sense of brotherhood. Suki Toka Apa (supporting and helping each other. Muki Nena (a sense of belonging and belonging)) This philosophy is a guideliness for the people in Kupang, namely